Room-temperature 1550-nm lasing from tensile strain N-doped Ge quantum dots on Si. Issue 12 (11th July 2020) - Li, Hongqiang; Wang, Jianing; Bai, Jinjun; Zhang, Shanshan; Zhang, Sai; Sun, Yaqiang; Dou, Qianzhi; Ding, Mingjun; Wang, Youxi; Qu, Dan; Du, Jilin; Tang, Chunxiao; et al.
Abstract : N-type heavy doping and tensile strain can significantly improve the luminescence efficiency of Ge materials. The active region of the quantum dot(QD) structure can realize high luminous efficiency due to its 3D carrier confinement. In this study, we constructed a Si-based QD array laser by introducing a 0.25% biaxial tensile strain and 4 × 10 19 cm − 3 N type heavy doping to Ge. A band-lifting method was proposed to determine the optimum doping concentration and thus improve the luminescence efficiency of Ge. To obtain accurate characteristics of the laser, we constructed a calculation model of three band transitions and all of the k-space quantum transitions of Ge and other relevant modified models. Results showed that the laser power was 5.31 μ W at a voltage of 2.5 V, and the laser wavelength reached 1519.4 nm at room temperature. The proposed laser can be used as a light source compatible with the Si-based CMOS process.